Human Rights Standards : Hegemony, Law, and Politics - Mutua, Makau (Book collections on Project MUSE., 2016)
How are human rights norms made, who makes them, and why? In Human Rights Standards, Makau Mutua traces the history of the human rights project and critically explores how the norms of the human rights movement have been created. Examining key texts and documents published since the inception of the human rights movement at the end of World War II, he crafts a bracing critique of these works from the hitherto underutilized perspective of the Global South. Attention is focused on the deficits of the international order and how that order, which is defined by multiple asymmetries, defines human rights in a manner that exhibits normative gaps and cultural biases. Mutua identifies areas of further norm development and concludes that norm-creating processes must be inclusive and participatory to garner legitimacy across various cleavages and divides. The result is the first truly comprehensive critical look at the making of human rights norms and standards and, as such, will be an invaluable resource for students, scholars, activists, and policymakers interested in this important topic.